200-year ice core bromine reconstruction at Dome C (Antarctica): observational and modelling results - F. Burgay; F. Burgay; R. P. Fernández; D. Segato; D. Segato; C. Turetta; C. Turetta; C. S. Blaszczak-Boxe; R. H. Rhodes; C. Scarchilli; V. Ciardini; C. Barbante; et al. (The Cryosphere, 2023)
Bromine enrichment (Brenr) has been proposed as an ice core proxy for past sea-ice reconstruction. Understanding the processes that influence bromine preservation in the ice is crucial to achieve a reliable interpretation of ice core signals and to potentially relate them to past sea-ice variability. Here, we present a 210 years bromine record that sheds light on the main processes controlling bromine preservation in the snow and ice at Dome C, East Antarctic plateau. Using observations alongside a modelling approach, we demonstrate that the bromine signal is preserved at Dome C and it is not affected by the strong variations in ultraviolet radiation reaching the Antarctic plateau due to the stratospheric ozone hole. Based on this, we investigate whether the Dome C Brenr record can be used as an effective tracer of past Antarctic sea ice. Due to the limited time window covered by satellite measurements and the low sea-ice variability observed during the last 30 years in East Antarctica, we cannot fully validate Brenr as an effective proxy for past sea-ice reconstructions at Dome C.